Otchizne geroyev-slava! - Kalenski, Vladimir Denisovich; Kalenskaya, Irina Viktorovna (Изогиз (Izogiz), 1961)
Colour lithograph from painting; portrait of astronaut; Earth from space in the background Original title: Отчизне героев слава! PO-0131